IMPLEMENTASI FULL DISK ENCRYPTION DENGAN ALGORITMA AES-XTS MENGGUNAKAN VERACRYPT - Dewi Laksmiati (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
Data security is currently a major concern in the world of data communication systems. Especially for important and sensitive data that must be kept confidential from unauthorized parties. There are several ways that can be applied to secure the data communicated. This paper will explain the effective security design for data communication using the AES algorithm for encryption and decryption. The National Institute of Standards and Technology (NIST) initiated a process to develop one in the Advanced Encryption Standard (AES), which also established an Advanced Encryption Algorithm to replace the 1998 Data Encryption Standard (DES) algorithm. Advanced Encryption Standard (AES) can be implemented through programs on software or embedded in hardware. In continuous development, NIST develop XTS as an advance standard that applies to full disk encryption. In this paper we will discuss the application of AES-XTS using the Veracrypt encryption application